Reliability of Distillations Simulation in Area of Low Concentrations - Genkova, P; Ninov, J; Petrov, p (Chemical Engineering Research Bulletin, 2008)
<!--[if gte mso 9]> Normal 0 false false false MicrosoftInternetExplorer4 <![endif]--><!--[if gte mso 9]> <![endif]--> <!--[if gte mso 10]> <![endif]--> The reliability of the simulation approach model for prediction of the concentration distribution of components in high purity distillation is questionable because according to various authors some elements of the equilibrium stage model become uncertain in the area of very low concentrations. For three systems the temperature and concentration profiles and the flow rates of the theoretical plates predicted numerically, are verified by experimentation in a quartz fractionating column. The coincidence of the experimental and computation results compared shows that the equilibrium-stage simulation procedure is reliable in solving technological problems of purification of specialty chemicals. For each studied system, a set of design and performance parameters that govern the production of high-purity substance, is found. Chemical Engineering Research Bulletin 11 (2007) 63-76